Les effets du fongicide Prévicure sur l’index mitotique de Vicia faba L (Ridomil) - Benmardja, Bahria; Harrt, Fatma (My University, 2018)
The purpose of our work was to study fungicide effect (Ridomil) on cell division of Vicia Faba roots the roots at different concentrations of fungicide (0.15 ; 0.3 ; 0.6%) for 48h comparing with control. Noticeable in the microscopic, knowing the cells in case of cell division first with its comparison with witness The ratio of mitotic index per equation is calculated according to the number of cellular deviations To find out whether this fungicide has an impact on cell division or not, we knew that each concentration of Ridomil increased cell division increases with it's a direct correlation relationship. Keyword: pestiside,
Keywords: pesticide; Ridomil; indice mitotique; Vicia faba.